The Impact of the COVID-19 pandemic on the mental health and social functioning of healthcare workers - Belcarz, Maria; Marczewska, Sylwia (Journal of Education, Health and Sport, 2023)
Introduction: The work of medical staff (doctors, nurses) is very stressful, especially during a pandemic. They often bear a lot of responsibility, work under time pressure and take care of a terminally ill patient. This unique time affects not only medical workers but also their families. The rules of functioning in a group and society are changing, and the possibility of exposure to infection by colleagues, relatives or friends is a risk factor for mental health problems. The aim of the study: The aim of the study was to analyse the prevalence of mental disorders and changes in the social functioning of medical workers during the Covid-19 pandemic. Materials and methods: Survey search using author-made questionnaire was conducted. The study group consisted of people from 22 to 66 years of age. The survey was anonymous. The study material was analyzed, consisting of 127 correctly completed questionnaires. Collected data was then transformed for statistical purposes and the correlations were examined using Mann-Whitney U test (men vs women). Results: Comparing the situation before the pandemic to the present one statistically significant increase in to experience stress at work for women. Nearly 90% of surveyed individuals are afraid of being infected with SARS-CoV-2 virus by a patient. Medical personnel (nurses, paramedics, doctors) are experiences stress (83%), fear (65%) and anxiety (76%) in the workplace. 10% of respondents took advantage of the psychological support. Conclusions: The mental condition and functioning in the society of medical workers is significantly impaired due to the ongoing Covid-19 pandemic. Medical workers are exposed to constant stress, anxiety, powerlessness and their social activity is disturbed.